ANALISIS NILAI MORAL DALAM NOVEL RASA KARYA TERE LIYE - Tri Ananda, Nadya; Kusyani, Diah; Lubis, Lailan Syafira Putri (Jurnal Bahasa Indonesia Prima (BIP), 2024)
This research is motivated by the fact that moral values are essential; novels, as written works of literature that contain moral values, can motivate readers. The purpose of the research is to describe the form of moral values in the novel Rasa by Tere Liye and the form of moral value delivery used by the author in the novel Rasa by Tere Liye. This type of research is library research. The results of this study found that the form of moral values contained in the novel Rasa by Tere Liye includes the form of moral values in human relationships with themselves, namely self-existence there are 7 data, self-esteem there are 2 data, self-confidence there are 4 data, fear there are 0 data, revenge there are 3 data, loneliness there are 1 data. The form of moral values in human relations with other humans in the social environment, namely solid friendship there are 3 data, betrayal there are 4 data; parental affection for children are 8 data; children's affection for parents there are 2 data; teacher advice to students there are 2 data. The form of moral values in human relationships with God, namely praying to God, has 0 data, and being grateful has 1 data. The form of conveying moral values used by the author in the novel Rasa by Tere Liye, namely the form of conveying moral values directly consists of 15 data, and the form of conveying morals indirectly consists of 5 data.